KADAR TOTAL FLAVONOID DAN AKTIVITAS ANTIOKSIDAN FRAKSI n-HEKSANA DAUN GAHARU (Gyrinops versteegii) - Parwata, I M. O. A.; Devanthi, N. M. D.; Dewi, I G. A. K. S. P. (Jurnal Kimia (Journal of Chemistry), 2022)
The use of herbal medicines as antioxidants has increased recently. One of them is  gaharu  leaf ( Gyrinops versteegii ).  Gaharu  plants have been widely used by people to treat various types of diseases. Papuan people have used the roots, bark and leaves of  gaharu  as malaria medicine and skin treatment. This research intended to ascertain the total content of flavonoids and antioxidant capacity of the n-hexane fraction in  gaharu  leaves’ extract. A total amount of 100 g dry powders of  gaharu  leaves, with water content of 8.59%, macerated with 96% ethanol, resulted in 10 g of concentrated extract obtained by evaporation using vacuum rotary evaporator. This extract then proceeded to the fractionation stage using solvents such as n-hexane, chloroform and ethyl acetate. The results obtained were 5.66 g of n-hexane, 2.23 g of chloroform, 0.85 g of ethyl acetate and 1.14 g of the remaining water extract. Phytochemical screening showed that the n-hexane extract positively contained flavonoids with the highest total flavonoid contents of 1557.66 mg QE/100 g. In-vitro test for the antioxidant activity of the n-hexane fraction utilizing the procedure of DPPH (1,1-diphenyl-2-picrylhydrazyl) showed the IC 50  value of 126.76 ppm. These results indicate that the n-Hexane fraction of  gaharu  leaves’ extract has a high total flavonoid contents and consists of active antioxidant compounds with medium capacity. Keywords:  oxidative stress, flavonoids, fraction n-Hexane, DPPH and antioxidant